Influence of COVID-19 on the company’s reinvestment in employee education and training - ?emerková, Šárka; Pokorná, Pavla; Malátek, Vojt?ch (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
This article deals with the results of two independent primary research studies in the field of the reinvestment activities of companies aimed at supporting employee education and training. Attention is focused on the reinvestment activities of companies and the direction of investment funds to individual areas with an emphasis on employee education and training. The article compares the situation before and after the first wave of the Corona crisis in the Czech Republic. Information on the structure and volume of corporate reinvestment is presented, as is information on reinvestment in employee development through selected training methods. The chi-square test was used for statistical analyses.